KONSEP PENDIDIKAN ISLAM INTEGRATIF DALAM PEMIKIRAN IKHWĀN AL-ṢAFĀ: SINTESIS EPISTEMOLOGIS ANTARA AKAL, WAHYU, DAN SPIRITUALITAS - Sahib, Muhammad Amin; Nur Asiah; Muzdalifah Sahib (Program Pascasarjana, UIN Alauddin Makassar, 2025)
This paper examines the educational ideas of the 10th-century Muslim philosophical group, Ikhwān al-Safā, as contained in their encyclopedic work Rasā’il Ikhwān al-Safā. This organization is known as a secret intellectual movement that sought to integrate Islamic religious values, Greek philosophy, and science within an educational framework. This study focuses on how the Ikhwān al-Safā viewed knowledge, its acquisition, classification, and the ideal figure of a teacher. It was found that the Ikhwān al-Safā adopted an esoteric approach to religion and positioned philosophy as a means to understand the inner meaning of revelation. In the context of education, they viewed knowledge as acquired through a combination of the senses, reason, and spiritual initiation. They also classified knowledge into mathematics, physics, and metaphysics, all of which were considered important for forming a complete human being. This paper shows that the Ikhwān al-Safā made an important contribution to Islamic educational thought, particularly in their efforts to unite reason and revelation in the process of seeking knowledge.